Development and Effectiveness of PNU3 NSM Mask of Preventing COVID-19 Infection Transmission among Thai Muslim Men: Siriphan Siriphan - Siriphan, Siriphan; Sangmanee, Rossukon; Mama, Samsuree; kurung, Subaidah; Madkasem, Nutcha; Singweratham, Noppacha (Princess of Naradhiwas University Journal, 2024)
Research and development aimed to develop and evaluate the effectiveness of PNU3 NSM mask of preventing COVID-19 infection transmission as well as determine the satisfaction of utilizing PNU3 NSM mask among Thai Muslim men. A purposive sampling was used to select 50 Thai Muslim men. The instruments of this study consisted of 4 parts: (1) demographic data of the samples, (2) PNU 3 NSM Mask water repellency test, (3) PNU3 NSM mask, and 4) the satisfaction measurement towards using PNU3 NSM mask that was validated contents by experts. The index of conformity between the question and the purpose equals 0.80, and the Cronbach's alpha coefficient value of 0.87. Data analysis was used frequency, percentage, average, and standard deviation. The results of this study found that there were four times that PNU3 NSM was developed to be suitable with Thai Muslim men. Three different types of PNU3 NSM mask after consulting sewing professionals were developed in the first phase of developing the mask. The second phase involved developing the PNU3 NSM mask and testing it with ten people who had the same criteria as the samples. The size and length of the mask strap were adjusted to be smaller and longer. The third phase involved revising and testing the PNU3 NSM mask with samples. The samples suggested lengthening the nose wire and mask strap to better fit with the sample face. The samples gave suggestions to adjust the size of mask strap and nose wire to be longer to be fit with the face. The PNU3 NSM mask was updated in the fourth phase based on the advice of the sample. The result of water repellency of PNU3 NSM mask by the moisture resistance of the fabric surface was determined in the fourth grade, which means it had a single drop of water or was lightly damp. The overall satisfaction rating was significantly high. The convenience of using the mask had the highest satisfaction rating (M= 4.50, SD= 0.670), followed by the mask's suitability (M= 4.48, SD= 0.544), safety when using the mask (M= 4.29, SD= 0.692), effectiveness when using the mask (M= 4.28, SD= 0.767), and attractiveness (M= 4.25, SD= 0.716). Therefore, the development of PNU3 NSM can enhance the effectiveness of preventing COVID-19 infection transmission.